Analysis of Students' Ability to make HOTS Questions Related to the Basic Physics Material that has been Studied - M. A. Martawijaya; Mahir Mahir (Jurnal Edukasi Terkini, 2025)
Purpose-This study investigates the ability of undergraduate physics students to create Higher Order Thinking Skills (HOTS) questions based on topics learned in basic physics. The focus is on how well students can formulate questions that require deeper thinking. Research Methodology/Design/Approach-The research involved 40 students who were asked to construct HOTS-based questions and participate in semi-structured interviews. The questions were categorized into four types of HOTS: inferential, interpretive, transfer, and hypothetical. Data were analyzed to understand the distribution and quality of the questions created. Findings-Most students were able to generate inferential (35%) and interpretive (30%) questions, which align closely with the content taught in class. However, fewer students produced transfer (20%) and hypothetical (15%) questions, which require applying knowledge in new contexts and engaging in speculative reasoning. Interviews revealed that students struggled with these latter types due to limited exposure to applied and creative thinking tasks. Originality/Value-This study offers a fresh perspective by focusing on students’ ability to create rather than just answer HOTS questions. The findings emphasize the need for teaching strategies that promote contextual, critical, and innovative thinking to better prepare students for real-world problem-solving and scientific inquiry.